2010
DOI: 10.1111/j.1399-3046.2010.01365.x
|View full text |Cite
|
Sign up to set email alerts
|

Platelet transfusion refractoriness attributable to HLA antibodies produced by donor‐derived cells after allogeneic bone marrow transplantation from one HLA‐antigen‐mismatched mother

Abstract: PTR is a serious problem in patients being treated for hematologic disorders. Two patients with acute leukemia developed PTR after allogeneic BMT from one HLA-antigen-mismatched mother attributable to HLA antibodies, which could not be detected in their serum before BMT. HLA antibodies, whose specificity resembled that of each patient, were detected in each donor's serum. Each donor had probably been immunized during pregnancy by their partner's HLA antigens expressed by the fetus, consequently, transplanted d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 10 publications
0
10
0
Order By: Relevance
“…23,24 Interestingly, three of four patients in this study showed a decrease in the platelet count, despite platelet transfusion on the previous day, on at least two occasions after testing HLA antibody-positive. It is difficult to specify the cause of platelet transfusion refractoriness in patients following allo-SCT because multiple factors, including thrombotic microangiopathy and infections, can be responsible for the occurrence of platelet transfusion refractoriness.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…23,24 Interestingly, three of four patients in this study showed a decrease in the platelet count, despite platelet transfusion on the previous day, on at least two occasions after testing HLA antibody-positive. It is difficult to specify the cause of platelet transfusion refractoriness in patients following allo-SCT because multiple factors, including thrombotic microangiopathy and infections, can be responsible for the occurrence of platelet transfusion refractoriness.…”
Section: Discussionmentioning
confidence: 59%
“…However, recently developed solidphase immunoassays, including the Luminex single antigen assays, allow the accurate identification and quantification of specific HLA antibodies, 22 which enable the comparison of the specificity of HLA antibodies between donors and patients. To date, only one report by Hatakeyama et al 23 demonstrated similar specificities between HLA antibodies that emerged in two patients and those found in their donors. Another case report by Nakazawa et al 24 showed that HLA antibodies with multiple specificities were detected in a patient undergoing SCT from an antibodypositive donor, but the specificity of antibodies in the donor could not be identified.…”
Section: Discussionmentioning
confidence: 87%
“…lesser extent, acute GVHD after HSCT from an unrelated donor, in the context of HLA class II mismatch in the GVH direction. To our knowledge, although anti-HLA donor immunization has been implicated in platelet transfusion refractoriness [19][20][21], the correlation with GVHD occurrence has not been evaluated previously.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, anti-HLA antibodies also may be detected in nulliparous females and nontransfused males [17,18], and thus specifically in HSCT donors. Apart from their role in induced platelet transfusion refractoriness [19][20][21], their impact on HSCT outcome has not yet been explored. Theoretically, recipient-specific anti-HLA antibodies (RSAs) might affect the development of GVHD [22].…”
Section: Introductionmentioning
confidence: 99%
“…70 Moreover, several case reports have suggested the occurrence of donor-derived HLA Ab production that was possibly associated with platelet transfusion refractoriness in these patients. 71,72 Although cellular immunity has been the main focus of the studies in SCT for decades, a revision of the role of humoral immunity may be warranted.…”
Section: Future Directionsmentioning
confidence: 99%